Meningkatkan Teknik Dasar Shooting Free Throw Bolabasket Melalui Metode Drill Variasi Latihan Wall Shooting pada Peserta Ekstrakurikuler Bolabasket Putra SMP - Ishaq, Iqbal Maghrobi; Januarto, Oni Bagus; Kurniawan, Ari Wibowo (Sport Science and Health, 2020)
Abstract: The purpose of this study was to improve the basic technique of shooting free throw for basketball extracurricular participants at Taman Adult Junior High School, Probolinggo City. The research method used is sports action research method. The research procedure used is planning, implementing, observing, reflecting. The subjects of this study were 10 basketball extracurricular members of the Taman Adults School Probolinggo City. The results of this study were obtained from 10 athletes, with details of the first 3 weeks for cycle 1 and the second 3 weeks for cycle 2. The results were obtained in the last week, 9 participants with a percentage (90%) were said to be complete by obtaining a score above the completeness standard and or achieving maximum completeness rate.Â Abstrak: Tujuan penelitian ini adalah meningkatkan teknik dasar shooting free throw peserta esktrakurikuler bolabasket SMP Taman Dewasa Kota Probolinggo. Metode penelitian yang digunakan adalah metode penelitian tindakan olahraga. Prosedur penelitian yang digunakan yaitu perencanaan, pelaksanaan, observasi, refleksi. Subjek penelitian ini adalah peserta ekstrakurikuler bolabasket SMP Taman Dewasa Kota Probolinggo yang berjumlah 10 orang. Hasil penelitian ini diperoleh dari 10 atlet, dengan rincian 3 minggu pertama untuk siklus 1 dan 3 minggu kedua untuk siklus 2. Hasilnya diperoleh pada minggu terakhir, 9 peserta dengan persentase (90%) dikatakan tuntas dengan memperoleh skor di atas standar ketuntasan dan atau mencapai angka ketuntasan maksimal.